A Coauthorship Network Analysis of Tourism and Hospitality Research Collaboration. (February 2013) - Ye, Qiang; Li, Tong; Law, Rob
As an essential part of knowledge development, research collaboration inspires knowledge acquisition and dissemination. As such, it attracts an increasing amount of interest from academic researchers. This article applies social network analysis to the investigation of research collaborations among tourism and hospitality scholars. Using articles published in six leading tourism and hospitality journals from 1991 to 2010, the empirical findings provide an overview of research collaborations in this field in terms of coauthorship networks. This study identifies some critical scholars in tourism and hospitality research collaborations. Result of a linear regression shows that research collaborations are significantly associated with researchers' research outputs. This article also proposes a new method to evaluate researchers' collaboration strategies on extroversive collaboration and introversive collaboration.